Enhancement of Ultraviolet Resistance of Polyaspartics - Karabacak, Bahar Demirtaş; Demir, Mustafa Muammer (01. Izmir Institute of Technology, 2024)
The degradation of polyaspartic ester (PAE) resins under ultraviolet (UV) exposure poses significant challenges for their long-term use in outdoor applications. This study investigates the enhancement of UV resistance of PAE resins through the incorporation of metal oxide particles as UV absorbers. The research aims to determine the efficacy of metal oxide particles in improving the UV protective properties of PAE resins. Experimental results demonstrate that the UV absorption values of resin dispersions containing metal oxide particles significantly increased compared to pure PAE resin. This enhancement may be attributed to the metal oxides' ability to absorb and scatter UV light, thereby reducing the transmission of harmful UV rays through the resin matrix. Various concentrations of metal oxide particles were tested, and the findings underscore the importance of achieving a homogeneous dispersion within the resin for optimal UV protection. The study concludes that the incorporation of metal oxide particles into PAE resins can remarkably enhance the UV resistance of PAE. The improved UV absorption characteristics make these modified resins more suitable for applications exposed to prolonged UV radiation. This research provides a foundation for further exploration into optimizing particle concentrations and dispersion techniques to maximize the UV resistance of polyaspartic ester resins while maintaining their transparency over visible region of the optical spectrum.

Poliaspartik ester (PAE) reçinelerinin ultraviyole (UV) ışınlarına maruz kalması, açık hava uygulamalarında uzun ömürlü kullanımlarında önemli zorluklar yaratmaktadır. Bu çalışma, UV soğurucu olarak metal oksit tanecikleri eklenerek PAE reçinelerinin UV direncinin artırılmasını araştırmaktadır. Araştırmanın amacı, metal oksit taneciklerin PAE reçinelerinin UV koruma özelliklerini iyileştirmedeki etkinliğini belirlemektir. Deneysel sonuçlar, metal oksit tanecikleri içeren reçine dispersiyonlarının UV absorpsiyon değerlerinin saf PAE reçinesine kıyasla önemli ölçüde arttığını göstermektedir. Bu iyileşme, metal oksitlerin UV ışığını absorbe etme ve saçma yeteneklerine bağlanmaktadır; böylece zararlı UV ışınlarının reçine matrisi içinden geçişi azalır. Çeşitli metal oksit tanecik konsantrasyonları test edilmiş ve optimal UV koruması için reçine içinde homojen bir dağılımın önemini vurgulamaktadır. Çalışma, metal oksit taneciklerinin PAE reçinelerine eklenmesinin, reçinelerin UV direncini etkili bir şekilde artırdığını sonucuna varmıştır. Gelişmiş UV absorpsiyon özellikleri, bu modifiye edilmiş reçineleri, uzun süreli UV ışınımına maruz kalan uygulamalar için daha uygun hale getirmektedir. Bu araştırma, poliaspartik ester reçinelerinin UV direncini maksimize etmek ve görünüt bölgede saydamlığını korumak için tanecik derişimini ve dispersiyon tekniklerinin optimize edilmesine yönelik çalışmalara temel oluşturmaktadır.
Poliaspartiklerin ultraviyole direncinin arttırılması
Thesis (Master)--İzmir Institute of Technology, Polymer Science and Engineering, Izmir, 2024
Includes bibliographical references (leaves. 79-85)
Text in English; Abstract: Turkish and English
Keywords: Polymers; Polymer Science and Technology